Advocating Islamic values and principles in the management of strata schmes in Malaysia: some notes for consideration - Mohamad, Mazliza; Sufian, Azlinor; Mohamad, Nor Asiah (Conference Master Resources, 2013)
Strata properties law in Malaysia came into existence in 1985 and was governed by the Strata Titles Act 1985 (“STA”). In furtherance to that, the Building and Common Property (Maintenance and Management) Act 2007 (“BCPA”) was introduced to regulate matters related to strata properties inter alia on the management and maintenance of common properties. Nevertheless, the Acts failed to a certain extent, in particular to address disputes arising from strata management and maintenance. The objective of this paper is to look into issues of management of strata properties and the available modes of resolving disputes from the Islamic perspective. This paper will illustrate some of the Islamic management practices and habits that can be adapted in the current management of strata properties to stimulate the maximum outcome of the management. It discusses the concept of joint ownership from the Islamic perspective and explains the roles of the parcel owners in strata building. The issues around the owners’ duties in respect of maintenance of property, the Islamic management practices and habits which can be employed by the management body in the strata building development will be discussed. It will also look into the method of settling disputes between the management body and the parcel owners from the perspective of the existing laws in Malaysia and Shari’ah. This paper focuses on the concept of Al-Takm (arbitration) and Al-Ift (advisory opinion) since there are some similarities to the functions of the Commissioner of Building (“COB”) under BCPA and Strata Titles Board (“STB”) under STA. The research method used in writing up this paper is the qualitative research in which it will be based on several revealed sources of Islam including, Al-Quran, Hadith and the writings of the traditional jurists as well as contemporary writers in Islamic jurisprudence. Some relevant statutes, rules, regulations, books, journals, articles, thesis, monographs, research grants reports, seminar papers, electronic materials and various newspaper reports will also be referred.